"THE PRACTICE OF INTRODUCING FAMILY LITERACY INTO SCHOOL EDUCATION" - Sattarova Feruza; Izzatullaeva Nargiza (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The study explores methods to enhance family literacy as a key factor in fostering successful collaboration between families and schools. It examines modern approaches, including interactive workshops, individual consultations, webinars, online courses, and digital platforms. Examples of successful global programs and regional cases are provided to demonstrate the effectiveness of these methods. The focus is placed on innovative approaches that promote parental involvement in the educational process and strengthen family-school partnerships.